Utilization of Rice Straw as Feed Substitution for Small Ruminants - Muchji Martawidjaja (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
The purpose of this paper is to review rice straw as ruminants feeds, problems in its utilization and alternatives to overcome the problems. Rice straw has great potency as animal feed resources, especially as sources of fiber. The availability of rice straw in several areas of the country as well as the amount of the rice straw ready to be used for ruminants make it a choice as source of feeds. Besides of its availability, rice straw considered to be low quality feeds, as recognized by low protein contents, high percentage of silica and lignin, therefore, the digestibility of rice straw is relatively low. Many treatments to improve rice straw has been conducted, where farmers in Southeast Asia prefer to treat rice straw using urea, because it can improve Nitrogen content  and  digestibility. Research to  improve rice  straw using  supplementation with  agriculture by  products as  well  as leguminosae forages has been conducted for ruminant feeds. Rice straw can be used as much as 10% for grass substitution and about 30% with the use of concentrate supplementation for sheep and goats.   Key words: Rice straw, sheep and goats